Al-Ruh Menurut Ibn Qayyim al-Jawziyyah - Abdul Rahim, Rohaida; Yakub, Asmadi (Jurnal Usuluddin, 2007)
This article discusses al-ruh in term of definition and discussion on several Quranic verses and al-Hadith. It also examines Ibn Qayyim al-Jawziyyah views on al-ruh based on his writing entitled, al-Ruh fi Kalam ala al-Ahya bi al-Dalail min al-Kitab wa al-Sunnah wa al-Athar wa Aqwal al-Ulama.